Akibat Hukum Terbitnya 2 Sertifikat Atas 1 Bidang Tanah (Tumpang Tindih/Overlapping) Ditinjau dari Pasal 263 KUHP - Ahmad Pahmi; Hartanto Hartanto; Uyan Wiryadi (Pusat Riset dan Inovasi Nasional, 2025)
One example of a case of falsified documents in the issuance of overlapping land certificates occurred in East Luwu Regency and was raised in court through Decision Number 90/Pid.B/2020/PN MII. In this case, it was discovered that land certificate falsification was carried out by a land mafia, resulting in the emergence of two certificates for the same plot of land. This practice not only harms the legitimate owner but also creates laws and gives rise to complex agrarian conflicts. This research uses a normative juridical method, with an approach based on laws and court decisions. The results show that the preservation was an intentional act carried out by one party, with the aim of controlling land rights that did not belong to him. In the decision, the perpetrator was found guilty and sentenced because it was also proven to have falsified documents, as stipulated in Article 263 of the Criminal Code (KUHP). From this case, it can be concluded that law enforcement against overlapping duplicate certificates is very important to ensure legal certainty and protection. Protection efforts for land rights holders are carried out through a land registration process that complies with procedures based on Law Number 5 of 1960 concerning the Principles of Agrarian Law. Compliance with these procedures can provide a strong basis for identifying legitimate rights holders and preventing future damage, including cases of overlapping certificates caused by document falsification. To prevent the recurrence of similar cases, it is necessary to improve the monitoring system and digitize land data comprehensively by the National Land Agency (BPN). An integrated digital-based land system can minimize the opportunity for the issuance of duplicate certificates for a single plot of land, because all land rights data can be accessed and disclosed transparently and in real time.